Current susceptibility status of Malaysian culex quinquefasciatus (Diptera: Culicidae) against DDT, propoxur, Malathion, and Permethrin - Low, V.L.; Chen, Chee Dhang; Lee, H.L.; Lim, P.E.; Leong, C.S.; Sofian-Azirun, Mohd (2013)
A nationwide investigation was carried out to determine the current susceptibility status of Culex quinquefasciatus Say populations against four active ingredients representing four major insecticide classes: DDT, propoxur, malathion, and permethrin. Across 14 study sites, both larval and adult bioassays exhibited dissimilar trends in susceptibility. A correlation between propoxur and malathion resistance and between propoxur and permethrin resistance in larval bioassays was found. The results obtained from this study provide baseline information for vector control programs conducted by local authorities. The susceptibility status of this mosquito should be monitored from time to time to ensure the effectiveness of current vector control operations in Malaysia.